2013
DOI: 10.5433/1679-0359.2013v34n3p1043-1054
|View full text |Cite
|
Sign up to set email alerts
|

Híbridos e variedades de milho submetidos à inoculação de sementes com Herbaspirillum seropedicae

Abstract: A fixação biológica de nitrogênio proporcionada por bactérias diazotróficas pode representar alternativa para a produção de milho em sistemas agrícolas mais sustentáveis ou de baixa utilização de insumos. Objetivando-se avaliar o crescimento, teor e acúmulo de nitrogênio em genótipos de milho, em função da inoculação das sementes com Herbaspirillum seropedicae, foi conduzido experimento em casa de vegetação avaliando-se 35 genótipos de milho híbridos simples, duplo, triplo e variedades. Para inoculação das sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Previous studies confirmed that inoculation of H. seropedicae promotes higher accumulation of N in the biomass of maize ( de Araujo et al., 2013 ; Alves et al., 2015 ; Breda et al., 2019 ; Dias et al., 2021 ). Interestingly, the greatest effects of the inoculation of this diazotrophic bacteria, especially in the metabolism of N, are reported under conditions of low availability of N. In addition, the application of the ZAE94 strain in maize seeds using peat as a carrier modified the plant response to N fertilization in a hybrid genotype, significantly increasing grain yield, mainly at the lowest tested dose of 0.8 mM of N ( Alves et al., 2015 ).…”
Section: Discussionmentioning
confidence: 53%
“…Previous studies confirmed that inoculation of H. seropedicae promotes higher accumulation of N in the biomass of maize ( de Araujo et al., 2013 ; Alves et al., 2015 ; Breda et al., 2019 ; Dias et al., 2021 ). Interestingly, the greatest effects of the inoculation of this diazotrophic bacteria, especially in the metabolism of N, are reported under conditions of low availability of N. In addition, the application of the ZAE94 strain in maize seeds using peat as a carrier modified the plant response to N fertilization in a hybrid genotype, significantly increasing grain yield, mainly at the lowest tested dose of 0.8 mM of N ( Alves et al., 2015 ).…”
Section: Discussionmentioning
confidence: 53%